Noise risk assessment on noise exposure among urban rail maintenance worker using personal monitoring method - J., M. Mifzal-Nazhan; Sani, Azlis; Nor-Azali, A.; Annuar, Y. Nur; Shahrul-Azhar, S.; Zulhelmi, Mohd (2023)
Urban Rail maintenance work usually involves a lot of daily mainte-nance work as proper maintenance must always be a priority for the rail industry to ensure the passengers are always comfortable and safe. These maintenance activities expose the technician to noise as they handle a lot of hand tools and machinery while performing their tasks. Noise Induced Hearing Loss (NIHL) is a major compensable occupational disease in Malaysia due to excessive noise-exposed above the permissible daily noise exposure limit. This study aimed to conduct Personal Monitoring as a part of Noise Risk Assessment (NRA) to meas-ure the level of noise exposure received among maintenance technicians in the excessive noise area. This study focuses on the areas and tasks involved in the Track Network Maintenance Hall (TNMH) and Track Vehicle Storage Building (TVSB) at one of the urban rail companies. Noise Risk Assessment was the se-lected method to measure the level of noise exposure among maintenance tech-nicians in the excessive noise area. The Personal Monitoring method was con-ducted as suggested in the ICOP provided by DOSH Malaysia. Data recorded shows that a total of 2 out of 3 technicians were exposed with a daily noise ex-posure limit exceeding 85dB(A) for 8 hours working shift. The exposure level was currently controlled by practicing the usage of a Personal Hearing Protector (PHP). Thus, this study confirmed that maintenance workers were exposed to high noise levels when performing their maintenance tasks